Effect of high vs. low volume of the nordic hamstring curl on hamstring muscle architecture and eccentric strength in soccer players: a systematic review and meta-analysis - Cholp, J.; Zemková, E. (Frontiers in Physiology, 2025)
Hamstring strain injuries (HSI) remain a significant problem in professional soccer, as this injury is the most prevalent. Nordic hamstring exercise (NHE) is the most researched exercise regarding its effect on modifiable factors of HSI. However, there is still debate about the minimal effective dosage for this exercise. This systematic review and meta-analysis aimed (1) to analyse the effects of low- and high-volume NHE on eccentric strength and hamstring muscle architecture in soccer players, and (2) identify gaps in the literature to guide future research. Three electronic databases (PubMed, Web of Science, Scopus) were searched, and 11 studies met the inclusion criteria. Pooled effect sizes (Hedges` g) and 95% confidence intervals (CI) were calculated using a random-effects model. High-volume NHE interventions significantly improved eccentric hamstring strength (g = 0.77, 95% CI 0.49-1.06, p < 0.001, I2 = 51%), fascicle length (g = 0.43, 95% CI 0.20-0.65, p < 0.001, I2 = 0%), and muscle thickness (g = 0.48, 95% CI 0.28-0.68, p < 0.001, I2 = 0%). Effects on pennation angle were non-significant (g = - 0.16, 95% CI -0.38-0.06, p = 0.16). Low-volume protocols significantly increased eccentric strength (g = 0.46, 95% CI 0.06-0.87, p < 0.05, I2 = 0%) but did not result in meaningful changes in fascicle length, pennation angle, or muscle thickness. For eccentric torque, neither high or low volume interventions produced significant effects (both g ˜ 0.04, p = 0.74, I2 = 0%). Control groups across all outcomes showed only trivial or negative changes. Results indicate that high volume of NHE (~2-3 sets of 8-12 repetitions/2-3 times per week) significantly increases peak eccentric strength, fascicle length of biceps femoris long head, and muscle thickness, while pennation angle shows only trivial increase. Low volume of NHE (~1-2 sets of 3-5 repetitions/1-2 times per week) shows a similar effect on peak eccentric hamstring strength, but there are no improvements in hamstring muscle architecture. Additionally, the effect of both types of volume on hamstring eccentric peak torque seems to be inconsistent. The variability of different testing methods on isokinetic strength and small correlations between other methods introduce challenges in comparisons with eccentric strength outcomes. A high volume of NHE seems to influence hamstring architecture adaptations better than low volume despite no differences in eccentric peak strength. Factors such as the player`s different level (amateur, semi-professional or professional), previous experience with NHE, and compliance significantly influence the training outcomes. Future research is needed to better determine the effect of low volume of NHE on the hamstring architecture adaptations in soccer players regarding previous experience with NHE and playing level. Furthermore, standardization of assessment tools and outcome measures is critical for future comparisons with isokinetic dynamometry.